Variability of Energy Dissipation and Shear Rate with Geometry in Unbaffled Surface Aerator - Bimlesh Kumar (Bulletin of Chemical Reaction Engineering & Catalysis, 2009)
The dissipation rate of turbulent kinetic energy () and shear rate (γ) are the key process parameters for mixing in surface aerators. At constant dynamic variables (rotational speed), both  and γ are greatly affected by the geometric parameters (impeller diameter, cross-sectional area of the tank, liquid height, rotor blade length and immersion height). By doing numerical computation by VISIMIX ®, present work analyzes the effect of non-dimensional (which is non-dimensionalized through rotor diameter) geometric parameters on e and g. With an increase in liquid height, there is an increase in the case of energy dissipation and shear rate values. In the case of tank area and blade length, it is vice versa. Energy dissipation and shear rate are not affected by the variation in immersion height of the impeller.